The Level of Mental Alertness and Its Relationship to Academic Self-Efficacy among Northern Border University Students (Journal Of Educational and Psychological Researches, 2023)
AbstractThis study aims at investigating the relationship between mindfulness and academic self-efficacy among Northern Border University students. To achieve this objective, the researcher adopted the correlative survey method for (97) students. For data collection, the researcher developed a mindfulness scale consisting of (42) items divided into seven topics, each one consisting of six items. The researcher developed an academic self-efficacy scale consisting of (20) items, adopting a five-point Likert scale. The results showed that there is a high level of mindfulness among students at the level of the seven units which formed the mindfulness scale; the conscious thinking unit showed the highest mean value of (4.08) whereas academic self-efficacy among students was at an average level. There is a positive relationship between the level of mindfulness and academic self-efficacy (i.e., 0.732), which is a high value that emphasizes the strong relationship with its means. The researcher recommended presenting training programs and sessions that aim at improving the mindfulness concept.